(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
This research focuses on the legal rules related to the financial independence of a company from that of its partners, in order to avoid the commingling of financial liabilities and the overlapping of claims between the company’s creditors and the company itself, and between the company’s creditors and its partners. This has led to the development of the principle of company independence and its separate legal personality, the adequacy of capital, sound company management and governance, controls preventing the malicious transfer of funds from the company for the purpose of liquidation, the prevention of fraudulent and deceptive practices intended to harm third parties (creditors), and the prohibition of unfair competition by managers with the company, among other modern rules in this field. Since the principle of company independence is a judicial principle, first appearing in the English case of Salmon v. Salmon, it was subsequently codified in the company laws of most Commonwealth countries and later adopted by other nations. Furthermore, many courts have recently issued rulings providing protection for individual creditors of companies undergoing audit, inspection, or liquidation. The rules mentioned above were referenced in the body of this research and reviewed and analyzed in accordance with the rulings of various courts. The research concluded with several key findings and recommendations, the most important of which are: Conclusion: The emergence of the principle of lifting the veil on the institutional independence of commercial companies is considered an exception to the application of the principle of independence and resulted from negative practices by companies not covered by the law. Recommendation: Legal advisors to companies should exercise due diligence, caution, and care when drafting company articles of incorporation and when issuing legal opinions to founding partners or company directors during incorporation or while managing the company’s affairs, in order to avoid situations that lead to the commingling of the partners’ financial liabilities with those of the company.